Length, Breadth and Thickness of the Pineal Gland (Bangladesh Journal of Anatomy, 2013)
Context: The pineal gland is capable of influencing or modifying the activity of the pituitary gland, islets of Langerhans, the parathyroid gland, adrenal gland and the gonads. The pineal gland through its hormone, melatonin influences many functions of the human, like circadian rhythm, mood, psychiatric disorder, sexual maturation, reproduction and aging. Melatonin, a potent antioxidant provides protection against damaging free radicals of oxygen. Various clinical problems occur due to abnormal melatonin secretion by the pineal gland. For the perfect and complete evaluation of various clinical conditions of the pineal gland, detailed morphological knowledge is essential. Study Design: Cross sectional analytical type of study. Place and period of study: Department of Anatomy, Dhaka Medical College, Dhaka from July 2009 to June 2010. Materials: 60 postmortem human pineal glands were collected from unclaimed dead bodies that were under examination in the morgue of the Department of Forensic Medicine, Dhaka Medical College Dhaka. Methods: The samples were divided into four different age groups i.e. Group-A (15-30 years), Group-B (31- 40 years), Group-C (41-50 years) and Group-D (> 50 years). Results: The mean±SD length of the pineal gland were found 8.11±0.83 mm in group A, 7.96±1.06 mm in group B, 7.51±0.55 mm in group C and 7.89±0.14 mm in group D. The mean±SD breadth of the pineal gland were found 4.39±0.34 mm in group A, 4.09±0.46 mm in group B, 4.12±0.58 mm in group C and 3.81±0.34 mm in group D. The mean±SD thickness of the pineal gland were found 2.52±0.64 mm in group A, 2.29±0.54 mm in group B, 2.14±0.32 mm in group C and 2.07±0.18 mm in group D. Conclusion: breadth and thickness of the pineal gland were found to be decreased with advancing age. DOI: http://dx.doi.org/10.3329/bja.v10i2.17286 Bangladesh Journal of Anatomy, July 2012, Vol. 10 No. 2 pp 63-67